The Bees of Rome: Representing Social and Spiritual Transition in Victorian Poetry - Wright, Jane (Journal for the study of religion, nature and culture, 2020)
In Book VI of the Aeneid, Virgil used bees to lgure human spirits in the Underworld. This was not the earliest association of bees with death and the afterlife, but it was the lrst such link in European literature. Virgil’s bees lgured those spirits who would become Aeneas’ descendants, future citizens of Rome. This moment in Pagan mythology had a remarkable literary afterlife in the work of (among others) Dante, Milton, Tennyson, Browning, C.G. Rossetti, and Michael Field, for each of whom (according to his or her religious faith) the bees were variously linked with Christ, Lucifer, France, Rome, the Saints, and both personal and national spiritual transition. Elucidating apian allusions in these poets’ works, I explain how the bees became poetical lgures for social and spiritual upheaval (at once dangerous and creative) and for the vital presence of the non-human (or angelic) in spiritual life.